The Awareness of Private Retirement Scheme and the Retirement Planning Practices among Private Sector Employees In Malaysia - Zabri, Shafie Mohamed; Ahmad, Kamilah; Lian, Angelina Ann Loy Hui (International Journal of Economics and Financial Issues, 2016)
Private Retirement Scheme (PRS) was first introduced in 2012 in supporting the private sector employees to prepare for their retirement. The main purpose of this exploratory study is to unveil the level of awareness of PRS and investigating factors influencing the retirement planning practices. This study applies quantitative approach with the use of survey questionnaires as the main instrument of data collection. Private sector employees from five private companies in Malacca was selected as respondents of this study. Data collected was analysed using descriptive analysis. In general, findings of this study shows that relatively, the level of awareness towards PRS is still low. In addition to that, only 77% of those that aware about this scheme have an interest to invest. Various factors were found to have an influence on the retirement planning practices private sector employees in Malaysia. Overall, this study shed some information on the awareness towards PRS among private sector employees in Malaysia and also factors influencing their current state of retirement planning practices. Keywords: Awareness, Private Retirement Scheme, Retirement Planning Practices, Private Sector Employees JEL Classifications: J26; J23; J38